Biosynthesis of phosphonic acids in tetrahymena - Warren, William A. (Biochimica et biophysica acta, 1968)
1. 1. The incorporation in vivo of 14C-labeled compounds into 2-aminoethylphosphonic acid and 2-amino-3-phosphonopropionic acid in Tetrahymena indicated a glycolytic intermediate precursor. 2. 2. Incorporation of 32P from phosphoenolpyruvic acid and from 2-amino-3-phosphonoprophonic acid into 2-aminoethylphosphonic acid was demonstrated in vitro with broken cell preparations. 3. 3. The data are consistent with an intramolecular rearrangment of phosphoenolpyruvic acid to form a phosphonic aci.